Compensation point phenomena in nanoscale Ising particles with high critical temperature. (2nd August 2020) - Kaneyoshi, T.
ABSTRACT: The phase diagrams and magnetizations of Ising nanoparticles with high critical temperature, consisting of atoms with a negative exchange interaction between the surface and the core, are investigated by using the effective-field theory with correlations. They show a compensation point below their critical temperatures, although they have not ferrimagnetic spin configuration. The effects of an applied transverse field to the nanoparticles are also discussed. One of them has exhibited the reentrant phenomena, although other does not show the phenomena. The reason is also discussed. The decoration for one of the nanoparticles is investigated. A compensation point is also found for the decoration.